PENGARUH KOMPETENSI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. SAMSUNG ELECTRONICS INDONESIA MAKASSAR - Andi Rahmawati; Andi Abdul Razak Ishak; Akbar Akbar (Journal of Innovation Research and Knowledge, 2021)
The purpose of this study was to determine the influence of organizational culture and competence partially and simultaneously on employee performance. This study uses quantitative research methods with data collection techniques through questionnaires and is supported by secondary data on employees at PT.Samsung Electronics Indonesia Makassar. The types of data used in this research are qualitative and quantitative data. Sources of data used in this study are primary and secondary data. The analytical method used is descriptive quantitative and multiple linear regression, correlation coefficient, coefficient of determination, and t test. The results of the study, both partially and partially, show that competence and organizational culture have a positive and significant effect on employee performance at PT.Samsung Electronic Indonesia Makassar.